WOAL: A Tool to Orchestrate Workflow Using An Abstraction Layer - Salleh F.H.M.; Bin I.A.; Sayuti A.B.; Omar R.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
E-learning; Problem oriented languages; Abstraction layer; Business Process; Complex workflows; Domain specific languages; Programming framework; System development; workflow; Workflow diagrams; Abstracting